Affirmative Action Untuk Mengurangi Disparitas Gender Dalam Politik di Kota Serang - arenawati arenawati; Nikki Prafitri; Yeni Widyastuti (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2020)
Affirmative action is a solution to reducing gender disparities in various fields including politics. Efforts to increase women's representation are important in providing justice for women for their political rights, by producing policies that protect women's political rights. The indicator set by the Sustainable Development Goals for gender equality is the number of women's representation in parliament. This research is motivated by the condition where the number of members of the Serang City DPRD for the 2019-2024 period is only 8 women from a total of 45 members or 17%, where this number has not met the 30% quota for women. This study aims to determine the affirmative action taken to reduce gender disparities in politics. The research method used in this research is descriptive qualitative with interactive data analysis techniques. This research finds that from a policy perspective, both the central and local governments have made efforts to carry out affirmative action in the political field even though women's participation in politics is still low. This is inseparable from obstacles in the form of public perceptions of the quality of female cadres, women's self-distrust, factors of family support and family background. The study also found that strengthening the role of political parties through socialization, gender-biased political education and the involvement of female cadres in organizational activities and community empowerment activities can have an effect on reducing the stigma of gender disparity in politics